Socio-cultural interpretation of the phenomenon of laughter in “The Joker” (2019) (Interpretation of the Western civilization man) - Nedeljković, Zoran (Sociološki pregled, 2021)
The author has given a socio-cultural interpretation of the phenomenon of laughter in the film “The Joker” (Todd, Phillips, 2019) as an individual as well as a social phenomenon of Western civilization. He considers the difference between the concepts of utopia, dystopia and utopistics as a possible solution to the problem that would avoid an optimistic and pessimistic view of the future of humanity. The author seeks a civilization parallel between the fictional world of film and the cultural elements of today. The necrophilic atmosphere of Gotham City is strikingly reminiscent of the spiritual lethargy that characterizes the postmodern metropolises of the 21st century. The fate of the film’s protagonist could afflict any individual on our planet if they came to the realization that they are a personality, that they have created themselves, and that on their own spiritual skin they have felt the misunderstanding of others who do not wish to stand out from the crowd. The author notes that many protesters against the governing structures of the oligarchy of states around the world have identified themselves in their protest with the Joker, an anti-hero who in a century of tolerance defends with laughter when he feels that his existence is threatened. In this film, the Joker is the personification of a diseased society. Todd Philips’ work is an attempt to draw attention to the fact that the stratification of the human community can lead to the breakdown of social relations, however much the governing establishment’s media seek to entertain and laugh at masses of proletarians and homeless people without a cultural identity through entertainment shows. The impact of the film, as a work of art, was visible immediately after its broadcast in public. The failed clown Joker could not cure himself with laughter because his laughing was “crying upside down” out of despair that was contrary to the hope of a man who could seek the meaning of his life in two Christian virtues: faith and love. However, the author of this text offers a solution by reminding of the way of life of a specific person, which would save the world from moral panic. He introduces us to a man with an accomplished existence of being a clown and a university professor at the same time – E. Kiphard (1923–2010), who lived to help fellow men with a mission to treat people with laughter rather than to defend them with the Joker’s unnatural and contagious laughter of an anti-utopian resident.